Odreševanje niča s posebnim ozirom na vlogo duhovnika v dramatiki Stanka Majcna - Gržan, Karel (2012)
Salvation of Nothing with Special Regard to the role of the Priest in the Drama of Stanko Majcen. The suffering of the innocent is a matter for many philosophers and religious awakens. In his plays, the playwright Stanko Majcen solves the problem of the painful states of helpless individuals, a study by Karl Grzan entitled Resolving the Nothing reveals. The entire dramatic oeuvre of otherwise versatile literary creator Stanko Majcen (1888-1970) is an attempt to answer why the helpless suffer. The politically engaged Majcen realizes that the company is incapable of resolving or answering its fundamental question. In the ever-increasing generality of the social, which is expressed in the form of chaotic, unrecognizable, manipulative, in Majcen's dramas, the only possible area in dealing with the suffering of the innocent is heard - ie. free autonomous individual (if we follow Kermauner's terminology). Such a personality alone does not escape the fact of nothing: it does not retreat into the loss of the crowd, but consciously enters the states of suffering as a salvific proximity. In his plays, Stanko Majcen also raises the issue of the priest as an autonomous individual within the institutional framework of the Catholic Church within (historically identifiable) models of his work. The question arises as to whether the church as an existing social structure is an auspicious place in which an individual (priest) can live as a free autonomous person with his or her personal story of vocation to salvage nothing in the concrete distress of a suffering person, or whether it remains primarily the preserver of external structures that are too often a hindrance to enter another, different? In dramatic terms, Majcen characterizes her in her practice as inadequate, but at the same time, with a mystical-theological vision, she points to the way out, not only to her, but to the entire social reality. Society and within its individual institutions are but a space of salvation happening, which is happening after and in a free autonomous individual. He can enter the realm of suffering, into the concrete zero point of the other, which proves to be his own salvation necessity. In Karl Gržan's study, we encounter the original messages of Stanko Majcen. In her own way, what Marja Boršnik summed up in her thought fulfills: "Greater silence will recognize him as a noble confessor." And Majcen himself believes and according to the Creator in his drama, the Revolution asserts: "They will find me whenever they find me needed. Among the palimpsests and parchments will be our charter."